The economic impact of using negative rake angle in high speed hard turning - Al Hazza, Muataz Hazza Faizi; Adesta, Erry Yulian Triblas (Design for Scientific Renaissance, 2013)
In high speed hard turning the cutting tool edge is under high pressure and the cutting forces are concentrating on the edge of the tool causing a breakage in the early stage of the tool life. Thus, by using a negative rake angle, the cutting forces will shift from the edge of the cutting tool to the flank face. The present work studies the economic factors of high speed hard turning (HSHT) by using negative rake angle. The influence of negative rake angle on tool life and power consumption has been discussed. AISI 4340 was used as work piece material;this steel is hardened to 60 HRC, machined by a mixed ceramic tool (Al2O-TiC). Totally 100 experiments were performed in order to measure the flank wear length, current, voltage, and power factor. The experiments were obtained with constant cutting depth (0.15 mm), constant feed rate (0.075 mm), constant cutting speed (250 m/min) and five different tool rake angles0o,-3, -6,-9 and -12).